Empowerment of Productive Zakat for the Welfare of the Poor in Bandar Lampung City - Anggoro Sugeng; Asmi Trisna Puspita (Jurnal Internasional Ekonomi Islam, 2022)
Zakat is one of the pillars of Islam that must be fulfilled by every Muslim. The distribution of zakat is still mostly consumptive and a small part is productive. This study aims to examine the distribution mechanism of productive zakat at BAZNAS Bandar Lampung City as well as to see the effectiveness of productive zakat to alleviate poverty which is equipped with the type of business run by Mustahiq. Collecting data in this study using interview techniques. The interviewees were the III Chairman of BAZNAS Bandar Lampung City, staff and Mustahiq in the Sukarame area of Bandar Lampung. The results of this study indicate that the Mechanism of Productive Zakat Distribution at BAZNAS Bandar Lampung City begins with Looking for Muzakki, Determining Mustahiq, Field Surveys, Providing Business Capital and the final goal is Mustahiq Mandiri. Meanwhile, the increase in Welfare of Mustahiq was felt directly by the respondents after the existence of venture capital from BAZNAS Bandar Lampung City. This is indicated by an increase in income compared to before. Most of the recipients of Revolving Business Capital have businesses in the form of food stalls and a small number have businesses as furniture and furniture craftsmen, craftsmen of shopping bags from used rope materials and other businesses.